Single-Stage Posterior Instrumentation for Progressive Tubercular Thoracic and Thoracolumbar Kyphosis. (December 2016) - Ahsan, Kamrul; Sakeb, Najmus
Purpose: To review the outcome of single-stage posterior instrumentation for progressive tubercular thoracic and thoracolumbar kyphosis in 45 patients. Methods: Records of 16 men and 29 women aged 20 to 59 (mean, 34.1) years who underwent single-stage posterior instrumentation for active thoracic (n=27) or thoracolumbar (n=18) tuberculosis by a single surgeon and were followed up for a minimum of 5 years were reviewed. Neurological status was evaluated using the Frankel grading system. Pain was assessed using the visual analogue score (VAS). Disability status was assessed using the Oswestry Disability Index (ODI). Outcome was graded according to the Kim and Lee criteria. Kyphosis at presentation, preoperation (after one month of conservative therapy), immediate postoperation, and 5-year follow-up was measured on radiographs to determine the kyphosis progression, correction of deformity, postoperative loss of correction, and residual deformity. Results: Respectively for 27 and 18 patients with thoracic or thoracolumbar involvement, at 5 years the mean VAS score improved from 5.5 to 1.9 (p<0.001) and from 6.8 to 1.5 (p<0.001), whereas the mean ODI improved from 60.8 to 11.7 (p<0.001) and from 57.5 to 7.6 (p<0.001). The outcome was excellent in 17 and 11, good in 7 and 5, and fair in 3 and 2 patients, respectively. The mean kyphosis progression from presentation to preoperation was from 20.2° to 26.2° and from 10.3° to 14.1°, respectively, whereas the corresponding mean predicted kyphosis progression was from 15.5° to 48.1° and from 13.8° to 50.4°. The respective mean correction of deformity was −8.1° and −8.5°; the respective mean residual deformity was 4.1° and 6.8°; and the respective mean loss of correction at 5 years was 1.9 and 1.9. Two patients had a dural tear, and 3 patients had a transient root injury. Two diabetic patients had superficial wound infection. One patient had downward migration of one rod at 30 months but remained asymptomatic. Conclusion: Single-stage posterior instrumentation combined with continued chemotherapy for a minimum 12 months is a viable option for early progressive thoracic and thoracolumbar tubercular kyphosis.